Chiral acidic amino acids induce chiral hierarchical structure in calcium carbonate - Wenge Jiang (Nature Portfolio, 2017)
Chiral structures are formed in numerous processes including biomineralization of calcium carbonate. Here, the authors demonstrate that the chiral, hierarchically-organized architecture of the calcium carbonate mineral, vaterite, can be controlled simply by the addition of chiral acidic amino acids.